PELAKSANAAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BEKASI - Andreas Noviyanto; Titin Rohayatin; Lukman Munawar Fauzi (Universitas Jenderal Ahmad Yani, 2019)
The implementation of public services at the Department of Population and Civil Registration of Bekasi Regency has not been optimal. If public services in the Department of Population and Civil Registration are seen from the implementation of the principles of Good Governance, such as aspects of accountability, transparency, and participation, they are still not optimal. This study uses a descriptive method with a qualitative approach. Observation data collection techniques and interviews with several informants related to research. The results of the study, which led to the implementation of the principles of Good Governance in population administration services at the Population and Civil Registration Service, have not run optimally, judging from the accountability of the mismatch between implementation and operational standards (SOP), as well as unclear service completion, not timely in providing services to the community. When viewed from the transparency aspect of the lack of availability regarding population administration services, the Department of Population and Civil Registration has not maximally used the official website in providing information to the public. And from the last aspect, namely participation, the community has not been fully involved in providing criticism and suggestions and the community is not involved in evaluating services. Keywords: Good Governance Principles, Accountability, Transparency, Participation, Population Administration Services